The Impact of Influence Aspects of Work and Organizational Commitment on Employee Life Satisfaction - Stefanus Happy Yanuar Hadi; Edi Hamdi (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Life satisfaction is an important thing for workers and companies, if life satisfaction is not fulfilled it will have an unfavorable impact. A good workplace experience results in an optimistic psychology and produces a high sense of happiness, and has an impact on life satisfaction. In the spillover theory, it is found that the influence aspect of work is determined by the surrounding environment. This research was conducted on Domestic Container Terminal workers in Indonesia. Where the sampling used is purposive sampling method with the criteria of employees who have a working period of more than 2 years. Data acquisition using survey methods, by means of questionnaire data distributed online using Google-form with Whatsapp social media. This study used a sample of 245 respondents with a total of 49 items. The results of the study can be used by companies, namely how to maintain the life satisfaction of workers, so that workers continue to get positive spillovers which can directly help the company to achieve the set targets. With this, employers can make future strategies in the field of Human Resources related to how to increase bonding with workers so that harmony between employers and workers is well created, one of which is by the way companies must pay attention to job stress experienced by workers by providing opportunities for workers to be involved in the organization, then providing work motivation by providing promotion and career development opportunities. It can be interpreted that everything leads to worker life satisfaction so that it can have a positive impact on individuals and organizations.